UNDERSTANDING CUSTOMERS - PROFILING AND SEGMENTATION - Mircea Andrei SCRIDON (Management & Marketing)
In any industry, the first step to finding and creating profitable customers isdetermining what drives profitability. This leads to better prospecting andmore successful customer relationship management. Any company cansegment and profile their customer base to uncover those profit drivers usingthe knowledge of their customers, products, and markets. Or they can usedata-driven techniques to find natural clusters in their customer or prospectbase. Whatever the method, the process will lead to knowledge andunderstanding that is critical to maintaining a competitive edge